The influence of the PNF method exercises on patterns of changes chosen antagonistic hip’s muscles of the patients with Parkinson’s disease - Rutowicz, Bartosz; Mirek, Elżbieta; Chwała, Wiesław (European Journal of Clinical and Experimental Medicine, 2005)
<span style="color: #010101; font-family: Lato, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Parkinson’s disease is the one of the most common neurological disease, after stroke and Alzheimer disease touching people above 50 years old. Apart from varied symptoms always comes to gait disorders. All consist on one group and create parkinson’s gait. The aim of the work was biomechanical assessment of the chosen muscle changes at the persons with PD and define effects of the therapy on change of the values biomechanical parameters. Put to the rest three patients (2 women and a man) with PD in aged 72–80 years old. The investigations were made at the Biokinetics Laboratory on the Antropomotorcity Cathedral at the Academy of Physical Education in Cracow. Vicon 250 system served to gait registration. Patient had for task of passages sure section with natural speed. The registration concerned 15 full cycles of walk. The length changes of the muscles were standarizationed with consideration of somatic build. The analysis concerned: m. iliopsoas – as a representative of the hip flexors and m. biceps femoris – as representative of the hip extensors. Both first and second investigation concerned „on” phase. On the basis of first investigation there was qualified main problem of every patient. In this way there was worked out for every patient the individual rehabilitation program in which included 15 therapeutic sessions. This program depended on therapy of the PNF method which is based on proprioceptive neuromuscular facilitation. To obtain the aim there serve techniques based on the movement patterns: shoulder, pelvic and upper or lower extremity. The investigation of walk after period of rehabilitation was repeated. On results of investigations it was founded that: – at persons with PD there is a displacement of muscles length changes responsible for hip movements in sagittal plane, – under the influence of physical exercises it was found improvement of the maximal and minimal muscle length, – under the influence of physical exercises the range of changes of chosen muscles does not undergo the essential change.